MUI Fatwa in Responding to COVID-19 Prevention in Indonesia: The Maqashid Sharia Perspective - Kasdi, Abdurrohman; Farida, Umma; Adim, Fauzan; Muslihun, Muslihun; Putra, D.I. Ansusa (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2023)
This paper examines the Indonesian Ulama Council (MUI) fatwa in responding and tackling the spread of COVID-19 in Indonesia using the Maqashid Sharia perspective. Maqashid Sharia is the objective of Islam contained in every enforcement of religious rules. The approach used is juridical-phenomenological. Juridically, a fatwa can be an alternative law in dealing with the spread of COVID-19. The phenomenological approach seeks and discovers the meaning of essential phenomena regarding handling COVID-19 cases in Indonesia. The result shows that Maqashid Sharia applied in the MUI fatwa in avoiding COVID-19 appear in four aspects: First, maintaining health and avoiding everything that may cause exposure to the disease. Second, people affected by the COVID-19 disease are obliged to isolate themselves so that transmission does not occur to others. Third, it prohibits activities involving public gatherings and worship at home to break the chain of distribution of the COVID-19 virus. Fourth, prohibit all actions that cause panic and cause public harm, such as buying up and hoarding necessities, hand sanitizers, and hoarding masks. These four aspects relating to the Maquashid Sharia, follow its core values, which ultimately guard the soul.